Variation of Velocity of Ions in a Magnetized Plasma Sheath for Different Magnetic Field (Journal of Nepal Physical Society, 2020)
The kinetic trajectory simulation method has been used to study ion velocity profile in a plasma sheath for varying magnetic field at fixed obliqueness. As the electrons have higher velocity compared to that of ions the wall is charged up negatively with respect to the core plasma. The negative potential then attracts the ions and repels electrons forming a thin positive space charge region in front of the wall. This positive space charge region, known as the ‘sheath’ separates the negatively charged wall from the quasineutral ‘presheath’ plasma. The ions moving towards the wall have to satisfy the Bohm criterion to ensure the stability of the overall plasma. The mean value as well as oscillation frequency of velocity of ions change as the magnetic field is varied from 1.5 to 10.5 mT. The maximum amplitude of normal component of velocity is almost independent of the magnetic field but the maximum amplitude of other components of velocity change and shows oscillating nature as the magnetic field changes.